Modeling what friendship patterns on facebook reveal about personality and social capital - Liu, Yong; Venkatanathan, Jayant; Goncalves, Jorge; Karapanos, Evangelos; Kostakos, Vassilis (My University, 2014)
In this study, we demonstrate how analysis of users' social network structure-a topic that has remained until recently inconspicuous within Human-Computer Interaction (HCI) research on social systems-can contribute to our understanding of Social Networking Services (SNS) effect on users. Despite a consensus that SNS enhance people's social capital, prior studies on SNS have provided inconsistent evidence on this process. In a multipronged study, we analyze personality, social capital, and Facebook data from a cohort of participants to model the extent to which one's SNS reflects aspects of his or personality and affects his bridging social capital. Our empirically validated model shows that empathy and conscientiousness influence the structural holes in one's social network, which in turn affects bridging social capital. These findings highlight the importance of network structure as an intermediary between one's personality and the social benefits one reaps from using SNS. Our work demonstrates how the implicit structural information embedded in users' social networks can provide key insights into users' personality and social capital. © 2014 ACM.
Keywords: Conscientiousness; Empathy; Facebook; Network structure; Personality; Social capital; Structural holes